A facile method for transparent carbon nanosheets heater based on polyimide. Issue 58 (31st May 2016) - Souri, Hamid; Yu, Seong Jun; Yeo, Hyeonuk; Goh, Munju; Hwang, Jun-Yeon; Kim, Seung Min; Ku, Bon-Cheol; Jeong, Young Gyu; You, Nam-Ho
Abstract : Transparent carbon nanosheet film heaters are fabricated by spin-coating of poly(amic acid) on quartz substrates following by carbonization process. These thin films show the transparency of 55–90% at 550 nm and sheet resistance of 14.7 to 1.6 kΩ sq −1 . Abstract : In this work, a novel film heater in nanometer-scale thickness based on catalyst-free and transfer-free carbon nanosheets (CNSs) with properties similar to graphene is fabricated. Here, poly(amic acid) (PAA), which is composed of several aromatic hydrocarbon rings, is used as the carbon precursor of CNS films. Altering the polymer concentration easily controls the morphological, optical, and electrical properties of the CNS films obtained by carbonization of PAA thin films. The CNS films with different thicknesses of 7.53–28.40 nm are simply prepared through spin-coating on a quartz substrate and post heat-treatment. Finally, their direct use as transparent film heaters is deeply investigated by considering electrical conductivity, temperature response rapidity, achievable maximum temperature, and electric power efficiency. For instance, an electrically conductive and optically transparent CNS film with 28.40 nm thickness exhibits excellent electric heating performance achieving well-defined steady-state maximum temperatures of 24–333 °C at low input electric power per unit film area of 0.027–1.005 W cm −2 in a relatively short time of ∼100 s.